Eyeglass Frame - Supported Nasal Prosthesis Rehabilitation: A Case Report - Haryo Mustiko Dipoyono; Murti Indrastuti; Titik Ismiyati; Putri Dhianita Pratiwi (Indonesia Prosthodontic Association, 2024)
Patients with facial defects resulting from neoplasm, congenital malformation or trauma can be restored aesthetically and emotionally with facial prosthesis using different materials and retention methods to restore missing tissues and help patients to overcome social, psychological difficulties, and function. A nasal prosthesis can re-establish esthetic form and anatomic contours for midfacial defects. For successful results, a lot of factors such as harmony, texture, color matching and blending of tissue interface with the prosthesis are important. This clinical report describes the details of a prosthodontic rehabilitation of a 52-years old female patient, who came to RSGM UGM Prof. Soedomo who received partial rhinectomy and complaints of esthetic appearance. The treatment plan was making nasal prosthesis using high temperature vulcanized (HTV) silicone rubber using an eyeglass frame and adhesive silicone. Mechanical devices such as eyeglass frames can provide more retention and support for the nasal prosthesis. One week after insertion, the patient felt comfortable and had no complaints. Nasal prosthesis can cover the nasal defect and help to improve the patient’s quality of life.